2013
DOI: 10.1007/s12262-013-0984-3
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Sewn Versus Stapled Esophagogastric Anastomosis in the Neck: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: The application of cervical esophagogastric anastomoses was of great concern. However, between circular stapler (CS) and hand-sewn (HS) methods with anastomosis in the neck, which one has better postoperative effects still puzzles surgeons. This study aims to systematically evaluate the effectiveness, security, practicality, and applicability of CS compared with the HS method for the esophagogastric anastomosis after esophageal resection. A systematic literature search, as well as other additional resources, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
(78 reference statements)
0
20
0
Order By: Relevance
“…The results showed that the time of operation in the mechanical group patients was significantly shorter than the manual group (9). However, some studies including meta-analysis showed no significant difference in surgical time between manual and mechanical anastomosis techniques (15,27). The results of the present study showed that the effective time of using a MMS technique for cervical esophageal anastomosis was significantly shorter than the manual procedure.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The results showed that the time of operation in the mechanical group patients was significantly shorter than the manual group (9). However, some studies including meta-analysis showed no significant difference in surgical time between manual and mechanical anastomosis techniques (15,27). The results of the present study showed that the effective time of using a MMS technique for cervical esophageal anastomosis was significantly shorter than the manual procedure.…”
Section: Discussionmentioning
confidence: 44%
“…Although, some studies including meta-analysis and systematic reviews have been performed to compare the effectiveness of HS and mechanical stapled techniques (linear or circular stapler), the superiority of one technique over the other is still controversial (14,15).…”
mentioning
confidence: 99%
“…Hsu et al compared the operating times entailed in manual and mechanical anastomoses and discovered that duration was signi cantly shorter in mechanical anastomosis technique than manual method (9). However, some studies, including meta-analyses, found no signi cant difference in surgical times between manual and mechanical anastomosis procedures (16,32). The results of the present study showed that the effective time of using a stapled technique for cervical esophageal anastomosis was signi cantly shorter than the manual procedure, This difference may be attributed to a number of reasons: use of numerous hand-sewn techniques described by surgeons (single-layer vs. multilayer anastomosis, interrupted vs. running suture techniques), intraoperative mishaps (e.g., poor alignment of sutures), and the skills of surgeons performing operations (9).…”
Section: Sugimura Et Al Used a Modi Edmentioning
confidence: 99%
“…This de ciency is exacerbated by the fact that although some studies, including meta-analyses and systematic reviews, have been conducted to compare the effectiveness of hand-sewn and stapled anastomosis techniques (through the use of linear or circular staplers), the superiority of one approach over the other remains a controversial issue (15,16). To address this matter, we compared the operation times and postoperative outcomes of transhiatal esophagectomy and cervical esophagogastric anastomosis performed via hand-sewn and stapled techniques over a year of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Stapled techniques have been presented in the past years as a means of minimizing the risk of anastomotic leakage and stricture (10)(11)(12). Collard et al used linear stapling devices in 1998 to carry out esophagogastric anastomosis, and Orringer applied structural modi cations to previously developed techniques to improve results (14), but whether the improved versions are superior remains a matter of debate.…”
Section: Introductionmentioning
confidence: 99%